Building Globally Competitive Human Resources: Integration, Competence, Technology, and Local Values - Kosasih, Nico (PT. Anagata Sembagi Education, 2025)
In the era of globalization and technological disruption, strengthening globally competitive human resources (HR) is an urgent need for national progress. This study aims to examine HR development strategies through an integrative approach that combines mastery of global competencies, utilization of digital technology, and preservation of local values. Using a qualitative-descriptive approach, this study highlights the importance of synergy between education, industry-based training, and strengthening local character in producing superior HR. The results of the study show that the development of globally competitive HR depends not only on technical skills and technological adaptation, but also on the internalization of local wisdom values as a shaper of identity and work ethics. The integration of aspects of competence, technology, and local culture is believed to be able to create HR that is not only ready to compete globally, but also remains rooted in national values. This study recommends the need for multi-sector collaboration between the government, educational institutions, and the business world in building a sustainable and contextual HR development ecosystem.